ANALISIS SISTEM PENGALIHAN PAJAK KENDARAAN BERMOTOR MENJADI PAJAK DAERAH - JUNIATI, EVI (Jurnal Akuntansi AKUNESA, 2013)
Transfer of motor vehicle tax to the local tax is expected to increase capacity to complete theneeds of local and regional spending and order to effective the administration and services.The research was conducted to determine the transfer system of motor vehicle tax to localtax. Objects in this research is the Department of Revenue.Data analysis technique used is descriptive analysis. The data used in report prepared by theMinistry of Finance of the Republic Indonesia. These results show that system of the motorvehicle tax is running well. The central government has had the concept and the steps thathave been planned and implemented in a consistent and sustainable.Keywords: Local tax, The transfer system of motor vehicle tax